Humanized Rodent Models for Cancer Research - Tian, Huimin; Lyu, Yanan; Yang, Yong-Guang; Hu, Zheng (Frontiers in Oncology, 2020)
As one of the most popular laboratory animal models, rodents have been playing crucial roles in mechanistic investigations of oncogenesis as well as anticancer drug or regimen discoveries. However, rodent tumors show different or no responses to therapies against human cancers and thus, in recently years, increased attention has been given to mouse models with xenografted or spontaneous human cancer cells. By combining with the human immune system (HIS) mice, these models have become more sophisticated and robust enabling in vivo exploration of human cancer immunology and immunotherapy. In this review, we summarize the pros and cons of these humanized mouse models, with a focus on their potential as an in vivo platform for human cancer research. We also discuss the strategies for further improving these models.